IMPLEMENTASI BLENDED LEARNING MODEL FLIPPED CLASSROOM: PERAN TEKNOLOGI DALAM PEMBELAJARAN MATEMATIKA DI TENGAH PANDEMI - Miftahul Huda; Risdiana Chandra Dhewy; Eka Nurmala Sari Agustina (JEDMA Jurnal Edukasi Matematika, 2021)
Blended learning is a combination of face-to-face and online learning with the help of technology. In this study, using mixed learning between synchronous and asynchronous learning, the learning model applied is the flipped classroom. This study aims to determine the activities of teachers and students, achievement of learning outcomes and student responses to learning using the flipped classroom model. This research is in the form of quantitative descriptive with a sample of 7 students from class X IPS-1 SMA Persatuan Tulangan. The data collection technique used was learning observation, learning result test in the form of post test and giving student response questionnaire. The results of observations of teacher activity during learning obtained a percentage of 84.37%, student activity in asynchronous learning through LMS Kelase, students were active, namely obtaining 83%, but when learning synchronously in the WA group student activities only obtained a percentage of 66.1% with the criteria being quite active. From student learning outcomes using flipped classroom trigonometric material, completeness of classical learning outcomes obtained 71.43% and declared incomplete because ≤ 75%. From the implementation of this learning, students gave a positive response.